Lava Discharge Rate of Sinabung Volcano Obtained from Modis Hot Spot Data - Kriswati, Estu; Solikhin, Akhmad (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.3.241-252To find out the long term data of Sinabung magma discharge rate and how long a series of eruption will be ended, time series of the volume of magma discharge is required. The dominant eruption product is pyroclastic flow that begins with the growth of the lava dome, so it is important to determine the volume of the lava dome over time. The method of determining the volume of magma issued is carried out by using hotspot data to resolve the problem of prevented visual observations and ground measurements. The heat and volume flux data expressed within a long period for a better view of variations in the Sinabung volcanic activity are based on thermal satellite data. Related lava dome volume and seismic data are also displayed to be compared with the heat and volume flux data. The numbers of thermally anomalous pixels and sum of radiance for all detected pixels at Sinabung during an overpass in the period of 2014 to 2018 have a downward trend. The discharge rates in the period of January 2014 to April 2015, Mei 2015 to March 2016, April 2016 to March 2017, and June 2017 to February 2018 are 0.86 m3/sec, 0.59 m3/sec, 0.36 m3/sec, and 0.25 m3/sec, respectively. Assuming no new intrusion or deformation rate changes, the lava discharge will be in the lowest rate in the early 2020s.